Analisis faktor yang mempengaruhi keputusan pembelian pada Bro D Towing Service Surabaya - Hamiseno, Alriga Rakareyhan; Purwanto, Sugeng (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Electronic word of mouth and advertising effectiveness are variables that can influence consumer purchasing decisions. This study aims to examine the concept of electronic word of mouth and the effectiveness of advertising on purchasing decisions at Bro D Towing Service which experienced a decline in sales in the last four months in 2021. The research method used was quantitative methods. The population in this study are consumers who have used the services of Bro D Towing Service Surabaya who have seen Bro D Towing Service Surabaya advertisements on social media, while the sample in this study was taken from a population of 65 respondents. with data analysis techniques using structural equation modeling and Partial Least Square (PLS) as analysis tools. The results of this study are known Electronic Word Of Mouth and the effectiveness of advertising have an effect on purchasing decisions. This means that the reviews on Google Business on Bro D Towing Service Surabaya influence consumers to make purchasing decisions and if an advertisement can be reached and accepted by all consumers, the advertisements that have been carried out by Bro D Towing Service Surabaya are effective and these consumers will always make decisions. to make a purchase.